Internet & popular culture: online fandom. - Ong, Minyu. (2008)
This research was carried out, looking at the nature and functions of OPC, based on data gathered from the online fan forums which are part of a sub-culture of OPC - online fandom. The main focus was on the focus was on the forums belonging to some of the most popular Chinese singers at the time of the research.